2004
DOI: 10.1017/s0021859604004186
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of 73As, 109Cd and 203Hg to the milk and tissues of dairy cattle

Abstract: SU MMARYBy a variety of exposure routes it is possible that the toxic heavy metals cadmium, arsenic and mercury could enter the diet of farm animals and hence contaminate food products derived from those animals. Therefore, there is a need to be able to assess the likely levels of contamination in animal tissues if exposed to contaminated feed and also to estimate how rapidly an animal will decontaminate once the source of contamination is removed from the feed. The development of dynamic models to predict cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…Beresford et al (1996Beresford et al ( , 1996c and Crout et al (2004) report data from single administration studies which they interpreted by fitting models to data for consecutive slaughter dates over a circa 1 year. Subsequent predictions of F f were made for differing periods of continuous administration; values incorporated into the database from these studies were the equilibrium or 1000 d predictions.…”
Section: Transfer To Meatmentioning
confidence: 99%
“…Beresford et al (1996Beresford et al ( , 1996c and Crout et al (2004) report data from single administration studies which they interpreted by fitting models to data for consecutive slaughter dates over a circa 1 year. Subsequent predictions of F f were made for differing periods of continuous administration; values incorporated into the database from these studies were the equilibrium or 1000 d predictions.…”
Section: Transfer To Meatmentioning
confidence: 99%
“…For cadmium, the value in Table 1 is an A a estimate derived by Crout et al (2004) from a compartment model based on an experimental study with three lactating cows given a single oral administration of 109 CdCl 2 . Urine and faeces were retained for 7 days and the cows slaughtered after 28 days and tissues analysed; milk was sampled throughout the 28 day experimental period.…”
Section: Values Derived From Literature Reviewmentioning
confidence: 99%
“…The concept has also been adopted within some heavy metal food chain models (e.g. Fayers, 1994) although others have suggested that equilibrium transfer coefficients are inappropriate because of the long biological half-lives of some heavy metal elements (Beresford et al, 1999;Crout et al, 2004).…”
Section: Introductionmentioning
confidence: 99%